Perceptions and Attitudes toward Online Mapping Services - Erskine, Michael A.; Gregg, Dawn G.; Karimi, Jahangir (The Journal of computer information systems, 2016)
Online mapping services, such as Google Maps and Bing Maps, have become increasingly popular. In addition to providing map, navigation, and directory information, such services provide third-party applications with a technology framework including geospatial-visualization capabilities. For instance, consumers often use location-based services and spatial decision support systems (SDSS) to locate the nearest restaurants, search for ideal homes, navigate specific routes, and effectively participate in car and bike sharing programs. Organizations utilize SDSS to perform retail site selection, manage global assets, and optimize supply chains. While geospatial-visualization is a vital capability of online mapping services, little is understood about how it impacts the acceptance of technology. Through a partial least squares analysis of 577 subject responses, this paper demonstrates that the user-acceptance of geospatial-visualization is influenced by utilitarian, hedonic, and cognitive measures. This paper concludes with a discussion of the implications of these results to research and practice.